Too Much Energy : The Perverse Effect of Low Fuel Prices on Firms - Cali, Massimiliano (World Bank, Washington, DC, 2019)
This paper provides novel evidence on the impact of changes in energy prices on manufacturing performance in two large developing economies -- Indonesia and Mexico. It finds that unlike increases in electricity prices, which harm plants' performance, fuel price hikes result in higher productivity and profits of manufacturing plants. The results of instrumental variable estimation imply that a 10 percent increase in fuel prices would lead to a 3.3 percent increase in total factor productivity for Indonesian and 1.2 percent for Mexican plants. The evidence suggests that effects are driven by the incentives that fuel price increases provide to plants towards replacing inefficient fuel-powered with more productive electricity-powered capital equipment. These results help to re-evaluate the policy trade-off between reducing carbon emissions and improving economic performance, particularly in countries with large fuel subsidies such as Indonesia and Mexico.